"Embedded" at hire? Predicting the voluntary and involuntary turnover of new employees. (11th November 2018) - Rubenstein, Alex L.; Kammeyer‐Mueller, John D.; Wang, Mo; Thundiyil, Tomas G.
Summary: Embeddedness theory has been invoked to describe factors that constrain employee turnover, such as fit with the environment, interpersonal links, and potentially sacrificed benefits. In contrast with previous assumptions that embeddedness requires considerable time to develop on the job, we extend theory by demonstrating how biographical characteristics (i.e., biodata), assessed at or before the point of hire, are related to individual's propensity to be embedded, while also showing how such characteristics predict one's future turnover likelihood. Beyond voluntary turnover, we also build embeddedness‐based theoretical explanations for involuntary turnover (i.e., terminations). To test these ideas, we conducted two studies at and before employees' point of hire, respectively: Study 1 examined how assessed biodata items of new employees relate to established embeddedness measures, whereas Study 2 linked the same biodata items assessed during the application process to employees' future involuntary, avoidable voluntary, and unavoidable voluntary turnover. Study 1 results revealed various biodata items predicted embeddedness in two distinct samples. In Study 2, results showed that biodata predicted turnover forms in unique ways. Our study highlights the utility of point‐of‐hire embeddedness propensity as a means to explain organizational exit, thereby demonstrating how organizations can use embeddedness tenets for employee recruitment and selection purposes.